Internal and External Environment Analysis in Escorting the Non-Physical Special Allocation Fund for Drug and Food Control in Lampung Province - Novia Hestiningrum; Widhyawan Prawiraatmadja (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Since 2020, the Indonesian FDA has given 319 districts/cities with a Non-Physical Special Allocation Fund for Drug and Food Control (DAK Nonfisik POM). The distribution of DAK Nonfisik POM to 419 districts/cities throughout Indonesia has been approved for 2021. The policy goal of DAK Nonfisik POM is to build regional capacity in the areas of pre- and post-market food home industry supervision, and licensing supervision in pharmaceutical service facilities. The implementation of DAK Nonfisik POM activities by Local Governments in Lampung Province must be escorted by the Balai Besar Pengawas Obat dan Makanan (BBPOM) di Bandar Lampung, which serves as the BPOM’s Technical Implementation Unit in Lampung Province. The purpose of this study is to analyze the internal and external environmental factor that affected the performance of BBPOM di Bandar Lampung related to its role in controlling the DAK Nonfisik POM in its working area. The type of research used is descriptive qualitative research using analytical tools, namely PESTEL framework, Resource-based View, and SWOT Analysis. The results showed some internal and external environment that affect on the performance of BBPOM in Bandar Lampung related to its role in escorting the DAK Nonfisik POM in Lampung Province.